(untitled) (Szociológiai Szemle, 2023)
This paper looks into the recruitment processes of a number of European companies and puts particular emphasis on the importance of the use of informal recruitment channels and of direct applications combined with waiting lists. Through this we seek to generate new knowledge about how European companies advertise vacant positions and recruit new employees, particularly low-skilled employees; and seek to understand whether the present recruitment strategies impact the employment of disadvantaged groups on the labour market. The research concludes that formal, informal and direct recruitment strategies need to be differentiated with regard to their impact on the employment of various groups of low-skilled facing difficulties on the labour market, and direct application seems to be a channel by which low-skilled jobseekers at a disadvantage on the labour market could achieve relatively balanced and promising results.